PENDAMPINGAN PROSES PRODUK HALAL (SELF DECLARE) DALAM PENGAJUAN SERTIFIKASI HALAL PRODUK USAHA MIKRO KECIL - Mahmud, Muhammad Daud bin (Al-Mulk: Jurnal Pengabdian Masyarakat, 2023)
The Halal Product Process (PPH) with a self-declare scheme is one of the facilities provided by the Indonesian government to small micro enterprises (UMK) to obtain halal certificates for their products. In 2023 the government through Badan Penyelenggara Jaminan Produk Halal (BPJPH) of the Ministry of Religion of the Republic of Indonesia has targeted 1 million UMK products to get halal certificates. To realize this target, the Ministry of Religion of the Republic of Indonesia then issued a Minister of Religion Regulation which requires assistance to business actors in applying for halal certification through a self-declare scheme. The purpose of this Pengabdian Kepada Masyarakat (PKM) is to assist business actors in applying for halal product certification by verifying and validating the halal statement submitted by business actors before being forwarded to the fatwa committee to determine the certificate. The assistance process begins with assisting business actors in submitting a risk-based business identification number (NIB) from the Investment Coordinating Board (BKPM) of the Republic of Indonesia. The process of assisting in submitting halal products begins after a business actor obtains an NIB. After carrying out intensive assistance for approximately 2 months, the business actor succeeded in obtaining a halal certificate for his product.Keywords: Halal Certification; Self Declare; Small Micro Business.